A comparison of time to exhaustion at VO2 max in elite cyclists, kayak paddlers, swimmers and runners - Billat, V.; Faina, M.; Sardella, F.; Marini, C.; Fanton, F.; Lupo, S.; Faccini, P.; de Angelis, M.; Koralsztein, J. P.; dal Monte, A. (Ergonomics, 1996)
A recent study has shown the reproducibility of time to exhaustion (time limit: tlim) at the lowest velocity that elicits the maximal oxygen consumption (vVO2 max). The same study found an inverse relationship between this time to exhaustion at vVO2 max and vVO2 max among 38 elite long-distance runners (Billat et al. 1994b). The purpose of the present study was to compare the time to exhaustion at the power output (or velocity) at VO2 max for different values of VO2 max, depending on the type of exercise and not only on the aerobic capacity. The time of exhaustion at vVO2 max (tlim) has been measured among 41 elite (national level) sportsmen: 9 cyclists, 9 kayak paddlers, 9 swimmers and 14 runners using specific ergometers. Velocity or power at VO2 max (vVO2 max) was determined by continuous incremental testing. This protocol had steps of 2 min and increments of 50 W, 30 W, 0.05 m s-1and 2 km-1 for cyclists, kayak paddlers, swimmers and runners, respectively. One week later, tlim was determined under the same conditions. After a warm-up of 10 min at 60% of their vVO2 max, subjects were concluded (in less than 45 s) to their vVO2 max and then had to sustain it as long as possible until exhaustion. Mean values of vVO2 max and tlim were respectively equal to 419 +/- 49 W (tlim = 222 +/- 91 s), 239 +/- 56 W (tlim = 376 +/- 134 s), 1.46 +/- 0.09 m s-1 (tlim = 287 +/- 160 s) and 22.4 +/- 0.8 km h-1 (tlim = 321 +/- 84 s), for cyclists, kayak paddlers, swimmers and runners. Time to exhaustion at vVO2 max was only significantly different between cycling and kayaking (ANOVA test, p < 0.05). Otherwise, VO2 max (expressed in ml min-1 kg-1) was significantly different between all sports except between cycling and running (p < 0.05). In this study, time to exhaustion at vVO2 max was also inversely related to VO2 max for the entire group of elite sportsmen (r = -0.320, p < 0.05, n = 41). The inverse relationship between VO2 max and tlim at vVO2 max has to be explained, it seems that tlim depends on VO2 max regardless of the type of exercise undertaken.